2016
DOI: 10.1021/acsami.5b11701
|View full text |Cite
|
Sign up to set email alerts
|

Partially Fluorinated Graphene: Structural and Electrical Characterization

Abstract: Despite the number of existing studies that showcase the promising application of fluorinated graphene in nanoelectronics, the impact of the fluorine bonding nature on the relevant electrical behaviors of graphene devices, especially at low fluorine content, remains to be experimentally explored. Using CF4 as the fluorinating agent, we studied the gradual structural evolution of chemical vapor deposition graphene fluorinated by CF4 plasma at a working pressure of 700 mTorr using Raman and X-ray photoelectron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 33 publications
3
71
0
3
Order By: Relevance
“…As example, the deconvolution of the spectrum for a 12.3 at% flake is shown in Figure 3a. [32] The additional peak between the D and G modes at 1456.5 cm −1 is generally attributed to the presence of F-containing covalent groups at the basal plane of the flakes, [16] and its large width is an artefact associated with the close proximity to the more intensive D and G modes. [32] The additional peak between the D and G modes at 1456.5 cm −1 is generally attributed to the presence of F-containing covalent groups at the basal plane of the flakes, [16] and its large width is an artefact associated with the close proximity to the more intensive D and G modes.…”
Section: Fluorographenementioning
confidence: 99%
See 1 more Smart Citation
“…As example, the deconvolution of the spectrum for a 12.3 at% flake is shown in Figure 3a. [32] The additional peak between the D and G modes at 1456.5 cm −1 is generally attributed to the presence of F-containing covalent groups at the basal plane of the flakes, [16] and its large width is an artefact associated with the close proximity to the more intensive D and G modes. [32] The additional peak between the D and G modes at 1456.5 cm −1 is generally attributed to the presence of F-containing covalent groups at the basal plane of the flakes, [16] and its large width is an artefact associated with the close proximity to the more intensive D and G modes.…”
Section: Fluorographenementioning
confidence: 99%
“…Specifically, the presence of edges in graphene can be decisive. To date, multiple methods for graphene fluorination have been extensively studied [8,10,[13][14][15][16][17][18][19][20][21] and it has been shown that the F content can be varied controllably by adjusting the reaction conditions. In thin film-based systems, however, the charge transport also is largely affected by the properties of edge/edge, edge/plane, and plane/plane junctions.…”
mentioning
confidence: 99%
“…The advantage of XeF 2 is the relative ease of manipulation compared to for example, F 2 . Other methods include, for example, treatment in CF 4 plasma at low pressures . Progressive fluorination of graphene in CF 4 plasma is shown in Figure .…”
Section: Synthesis Of Graphene Derivativesmentioning
confidence: 99%
“…Additionally, the defects and undesired system downtime associated with NH 4 Cl will reduce productivity. More importantly, some applications prefer a halide-free process [4,135,136,137]. …”
Section: Challenges Of Sinx Aldmentioning
confidence: 99%